HUBUNGAN POLA MAKAN DENGAN KADAR ASAM URAT (GOUT ARTRITIS) PADA USIA DEWASA 35-49 TAHUN - RIRIN FITRIANI; LIRA MUFTI AZZAHRI; MUHAMMAD NURMAN; M. NIZAR SYARIF HAMIDI (Universitas Pahlawan Tuanku Tambusai, 2021)
Hyperuricemia occurs due to an increase in uric acid production in metabolism or a decrease in uric acid excretion, which accumulates in large quantities in the blood, which triggers the formation of needle-shaped crystals, one of which is caused by diet. The purpose of this study was to determine dietary patterns with uric acid levels (gout arthritis) in adults aged 35-49 years in the working area of the Bangkinang Kota Health Center in 2020. This type of research is descriptive analytic with a cross sectional design. The population in this study were adults aged 35-49 years in the working area of the Kota Bangkinang Community Health Center with a total of 110 people with a sample of 52 people. The sampling technique used accidental sampling. Data collection tools in research using a questionnaire. This study used univariate and bivariate analysis with the chi-square test. The results showed that most of the respondents had a bad diet, most of the uric acid levels were abnormal. There is a relationship between diet and the incidence of uric acid in the working area of the Kota Bangkinang Community Health Center with a p value of 0.003. It is hoped that patients and their families pay more attention to and carry out a good diet and pay attention to foods that can be consumed and cannot be consumed by sufferers of arthritis gout.